2019
DOI: 10.2196/10992
|View full text |Cite
|
Sign up to set email alerts
|

Impact of New Technologies for Middle-Aged and Older Patients: In-Depth Interviews With Type 2 Diabetes Patients Using Continuous Glucose Monitoring

Abstract: Background Continuous glucose monitoring (CGM) uses subcutaneous sensors and records the average interstitial sensor current every 5 min in the recorder; data are subsequently exported to a computer 4 to 7 days later when calibration with self-measured blood glucose is made retrospectively. How middle-aged and older patients perceive the added technology intervention is not clear. Objective The study aimed to understand the factors associated with the adoption of new te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Others have similarly found that patients with T2DM view CGM technology as an efficient tool to visualize blood glucose readings, monitor trends, and prompt dietary change [ 33 ]. Our study is unique as it combines CGM use with low-carbohydrate diet coaching.…”
Section: Discussionmentioning
confidence: 99%
“…Others have similarly found that patients with T2DM view CGM technology as an efficient tool to visualize blood glucose readings, monitor trends, and prompt dietary change [ 33 ]. Our study is unique as it combines CGM use with low-carbohydrate diet coaching.…”
Section: Discussionmentioning
confidence: 99%
“…“All I can answer is that I am doing this [experiment] for my own good! And I also want to know where the problem lies!” 32 …”
Section: Resultsmentioning
confidence: 99%
“…We did not explore reasons why individuals declined to participate and this is something that could be investigated in future work. To our knowledge, few previous studies have explored barriers to and facilitators of CGM technology as a diabetes self-management tool among patients with T2DM [ 36 , 37 ]. Although CGM technology can empower and motivate patients with type 1 diabetes mellitus who are accustomed to routine self-monitoring of blood glucose to guide insulin dosing [ 36 ], CGM technology may enhance diabetes-related distress, which is a known barrier to T2DM self-management [ 38 ].…”
Section: Discussionmentioning
confidence: 99%